232 COVID stress and sleep disturbance among a racially/ethnically diverse sample of adolescents: Analysis from the NESTED study. (3rd May 2021) - Seixas, Azizi; Honaker, Sarah; Wolfson, Amy; Wahlstrom, Kyla; Owens, Judith; Wong, Patricia; Saletin, Jared; Tsvetovat, Maksim; Carskadon, Mary; Meltzer, Lisa
Abstract: Introduction: Using data from the Nationwide Education and Sleep in TEens During COVID (NESTED) study (N=6, 578), we investigated if race/ethnicity (64.6% were White and 35.4% identified as a racial/ethnic minority, mixed, or "other") and community social vulnerability affected the association between COVID stress and sleep disturbance. Methods: Data on sociodemographic factors (age, race, sex, grade, zip code [for neighborhood social vulnerability index, SVI]), COVID-related stress, depression, anxiety, instructional format (online, in-person, or hybrid), and sleep disturbance (PROMIS Pediatric Sleep Disturbance) were captured through an online survey. Descriptive and inferential analyses (Hierarchical Binary Logistic Regression (HBLR), SPSS v. 25) in 4171 adolescents examined associations between sleep disturbance and COVID-related stress, adjusting for race, sex, SVI, grade level, learning format, household density, and mental health factors. Results: Sleep disturbance was prevalent among adolescents (89% above average, T-score >50); about two-thirds (64.4%) reported greater stress due to the pandemic. Compared to White (88.5%) adolescents, sleep disturbance was more common in Black (91.2%), Hispanic (90.5%), American Indian/Alaska native (95.1%), and Mixed (92.3%) and less common in Asian (83.9%) adolescents. Chi-square analysis indicated that both race/ethnicity (□2 = 14.96, p<.05) and SVI (□2 = 8.34, p<.05) had an effect on sleep disturbance. HBLR analysis indicated that compared to pre-pandemic, adolescents reporting "little stress" (OR=.70, 95% CI= .49-.99, p=.04) or "the "same amount of stress" (OR=.64, 95% CI= .47-.89, p=.007) had lower odds of sleep disturbance. Higher depression (OR=1.06, 95% CI=1.04-1.07, p<.001) and anxiety (OR=1.05, 95% CI=1.04-1.07, p<.001) symptoms increased odds of sleep disturbance, while male gender lowered odds of sleep disturbance (OR=.11, 95% CI=.015-.86, p<.05). Overall, race/ethnicity (p=.44) and SVI (p=.45) did not independently predict sleep disturbance. Race/ethnicity stratified analyses indicated that for Black and Hispanic adolescents, being in grades 11/ 12 and depression predicted sleep disturbance; and for Asian adolescents SVI and anxiety predicted sleep disturbance. Conclusion: COVID-related stress and symptoms of depression and anxiety are associated with sleep disturbance. We observed differences in sleep disturbance across racial/ethnic groups and neighborhood social vulnerability strata, for specific racial/ethnic groups. Support (if any): AS was supported by funding from the NIH (K01HL135452, R01HL152453)